Governing Privacy in Knowledge Commons - Rose Sanfilippo, Madelyn; Frischmann, Brett M.; Strandburg, Katherine J. (Social Sciences, 2021)
Scholars from various disciplines explore privacy governance using the Governing Knowledge Commons framework. Case studies drawn from contexts such as academia, social media, mental health, and IoT provide insights into how privacy shapes community knowledge production. This title is also available as Open Access on Cambridge Core.